The response of Arctic warming to aerosols - Di Chen; Qizhen Sun (Environmental Research Letters)
Aerosols are increasingly recognized as critical components in global climate dynamics, yet their complex spatiotemporal variability and observational uncertainties present significant challenges in assessing their climatic impacts, particularly in the context of Arctic warming. This study leverages the latest reanalysis data and single-forcing ensemble models to investigate the origins of Arctic aerosols and their contribution to regional warming over the period from 1980 to 2023. Our findings indicate that aerosols in the Arctic predominantly originate from mid-to-high latitude regions through radial transport. Overall, aerosols mitigate some of the warming effects induced by greenhouse gases, accounting for 19% of Arctic warming, with notable variations among different aerosol types. We demonstrate that aerosols influence cloud formation and alter surface net solar radiation, thereby significantly affecting heat flux and contributing to Arctic warming. Furthermore, we project future Arctic temperature responses to aerosols, offering a theoretical foundation for advancing research on global climate change.